Contemporary visions of Kant´s political philosophy - Milicic, Nenad (Jihočeská univerzita, 2022)
The research will start as an overview of the ideas from Kants theoretical and practical elements of transcendental idealism and continue with his philosophy of law insights. It will encompass the analysis of the Critique of Pure Reason for the section on Kants theoretical philosophy, Critique of Practical Reason and Groundwork of the Metaphysics of Morals for the section on Kants moral philosophy and the first part of the Metaphysics of Morals called the Doctrine of Right regarding Kants philosophy of law, alongside with the secondary literature sources. Furthermore, the thesis will aim to examine Kants essays published continuously in the Berliner Monatsschrift journal in the last two decades of the eighteenth century.
Contemporary visions of Kant´s political philosophy
Keywords: Immanuel Kant; visions; philosophy; political philosophy; transcendental idealism; analysis; Immanuel Kant; visions; philosophy; political philosophy; transcendental idealism; analysis